Regulating access to international large-value payment systems - Cornelia Holthausen; Thomas Rønde (European Central Bank (ECB), 2000)
This paper studies access regulation to international large-value payment systems when banking supervision is national task. We focus on the choice between net settlement or imposing real time gross settlement. As a novel feature, the communication between the supervisors is endogenized. It is shown that the national supervisors' preferences regarding the settlement method are not perfectly aligned. As a result, systemic risk is excessive under public regulation. Still, leaving access regulation to the private banks can only be optimal if they have superior information about the risk of their foreign counterparty in the settlement system.
Keywords: E58; G20; G28; 330